2021
DOI: 10.1590/1413-81232020261.30592018
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre casos de hepatite A e áreas de inundação, município de Encantado, Rio Grande do Sul, Brasil

Abstract: Resumo A relação entre os desastres de origem hidrometeorológicos e a saúde das populações atingidas ainda é pouco abordada no Rio Grande do Sul (RS), Brasil. A Hepatite A é uma doença que envolve questões sanitárias e do meio urbano, sendo uma doença do tipo evitável. Esse estudo tem como objetivo analisar a relação entre áreas de inundação e a ocorrência de doenças de veiculação hídrica, neste caso, a Hepatite A. Foi estruturado um banco de dados dos casos confirmados de Hepatite A e de eventos de inundações… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
4
0
3
Order By: Relevance
“…García et al (2017) reported that the large amount of debris generated after a disaster represents a risk factor for the population that have to face health problems and the need of rebuilding the city. Silveira et al (2021) verified an increase of almost 300% in the record of waterborne diseases in the 3 months after the occurrence of flooding in an urban area in Brazil. The authors highlighted the importance of formulating and implementing policies to prevent disease outbreaks after hydrometeorological disasters.…”
Section: Introductionmentioning
confidence: 78%
“…García et al (2017) reported that the large amount of debris generated after a disaster represents a risk factor for the population that have to face health problems and the need of rebuilding the city. Silveira et al (2021) verified an increase of almost 300% in the record of waterborne diseases in the 3 months after the occurrence of flooding in an urban area in Brazil. The authors highlighted the importance of formulating and implementing policies to prevent disease outbreaks after hydrometeorological disasters.…”
Section: Introductionmentioning
confidence: 78%
“…Somado a isso, o alto índice pluviométrico, junto à abundância de água e à poluição dos recursos hídricos promovem maior contato das pessoas com fluidos poluídos, propiciando a contaminação. Além disso, a ocorrência de eventos extremos -como enchentes e alagamentos teriam um papel importante na transmissão da doença (WHO, 2019;Silveira et al, 2021).…”
Section: Resultsunclassified
“…Similarly, the relationship between flood areas and hepatitis A was explored in a study conducted by Silveira et al 17 . They structured a database of confirmed cases of hepatitis A and flood events in the municipality of Encantado, Rio Grande do Sul, Brazil, between 2012 and 2014.…”
Section: ● Public Health Implications and Potential Infectious Diseas...mentioning
confidence: 99%